Relation between extent of coronary artery disease and blood viscosity. Issue 6215 (8th March 1980) - Lowe, G D; Drummond, M M; Lorimer, A R; Hutton, I; Forbes, C D; Prentice, C R; Barbenel, J C
Abstract : Blood viscosity (shear rate 100/s) and its major determinants (packed cell volume, plasma fibrinogen concentration, and plasma viscosity) were measured before coronary angiography in 50 men aged 30-55 and related to the extent of coronary artery disease. Twenty-six men had extensive disease (stenosis of two or three major coronary vessels), and 24 had either stenosis of one vessel or no stenosis. The 26 men with extensive disease had significantly higher mean blood viscosity than those with mild or no disease and 25 healthy controls (p less than 0.001). The increased viscosity was due partly to a higher packed cell volume and partly to a higher fibrinogen concentration; plasma viscosity was not significantly increased. These differences could not be explained by smoking history. These results suggest an association between increased blood viscosity and extensive coronary artery disease in men, which merits further investigation.